A MORAL PROBLEM ABOUT PRAYER. Issue 36 (17th December 2013) - Smilansky, Saul
<x content-type="archive" xml:space="preserve">Abstract</x> At a time of acute danger, people commonly petition God for help for themselves or their loved ones. Such prayer seems natural and, indeed, for believers, reasonable and acceptable. But once we closely examine what is actually happening in such situations, we see that frequently such prayer is not morally innocuous. I present a number of examples which illustrate the difficulty, and argue that even assuming the benevolence of the deity does not suffice to make such prayer legitimate.